Study on Optimization of Ultrasonic Extraction Process for Benzoic Acid as a Harmful Component in Paeonia lactiflora Pall - Chen, Shangyue; Guo, Guiming; Chen, Gang; Zhai, Yanxin; Xie, Jingliang; Zhao, Xu; Cai, Mingxue; Zhou, Xuegang (Chinese medicine and natural products, 2025)
To optimize the ultrasonic extraction process for benzoic acid as a harmful substance in Paeonia lactiflora Pall. (P. lactiflora Pall.).Methanol and ethanol solutions at different concentration gradients (25, 50, 75%) were prepared to investigate the effects of extraction solvents on the extraction efficiency of benzoic acid. The influences of ultrasonic frequency (35, 50 Hz), ultrasonic power (40, 60, 80, 100 W), ultrasonic time (10, 20, 30, 40, 50, 60 minutes), and ultrasonic temperature (20, 30, 40, 50°C) on the extraction efficiency were examined. Orthogonal experiments were conducted to analyze the effects of temperature, time, and ultrasonic power on the extraction efficiency and to screen the optimal ultrasonic extraction process.Various influencing factors had certain effects on the extraction efficiency of benzoic acid from P. lactiflora Pall. Single-factor analysis revealed that 25% methanol, ultrasonic frequency of 50 Hz, ultrasonic power of 40 W, ultrasonic time of 10 minutes, and ultrasonic temperature of 30°C yielded the highest extraction efficiency for benzoic acid. The order of influence of different factors on the extraction efficiency was temperature > time > power. The optimal conditions obtained from orthogonal experiments were: extraction solvent of 25% methanol, ultrasonic frequency of 50 Hz, ultrasonic time of 20 minutes, ultrasonic power of 40 W, and ultrasonic temperature of 30°C.Under the conditions of 25% methanol as the extraction solvent, ultrasonic frequency of 50 Hz, ultrasonic time of 20 minutes, ultrasonic power of 40 W, and ultrasonic temperature of 30°C, the extraction efficiency of benzoic acid from P. lactiflora Pall. was the highest. This method offers advantages such as simple operation, small sample size requirement, and low solvent consumption, providing a reliable analytical approach for quality control and safety evaluation of P. lactiflora Pall.
Keywords: Paeonia lactiflora Pall.; benzoic acid; ultrasonic extraction; process optimization